Pengaruh Kompensasi, Kepuasan Kerja, dan Peluang Promosi terhadap Retensi Karyawan di Industri Manufaktur di Jawa Timur - Ida Farida; Nanny Mayasari; Anas Romzy Hibrida (Jurnal Bisnis dan Manajemen West Science, 2024)
This study investigates the effects of compensation, job satisfaction, and promotion opportunities on employee retention in the manufacturing industry in East Java. A quantitative approach was utilized, involving 180 respondents from various manufacturing companies. Data were collected using a structured questionnaire and analyzed with Structural Equation Modeling (SEM) using Partial Least Squares (PLS). The findings reveal that compensation has the strongest positive influence on employee retention, followed by job satisfaction and promotion opportunities, all of which are statistically significant. These results highlight the importance of competitive compensation packages, fostering a supportive work environment, and providing clear career advancement opportunities to enhance retention. The study offers practical recommendations for human resource managers to improve employee retention strategies in a competitive manufacturing environment. Future research could explore additional factors and qualitative perspectives to provide deeper insights into retention dynamics.